Application of chiral single-walled carbon nanotube in electrochemical oxygen evolution reaction
Structural control and active sites of carbon-based metal-free catalysts in OER are solved by using heteroatom-free, defect-free chiral single-walled carbon nanotubes (6,5)-SWNTs and (7,6)-SWNTs. Characterization problems achieved efficient and stable electrocatalytic performance, especially excellent performance under water cracking and light induction.
Patent Information
- Application Number
- CN202311782007.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-22
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the application of carbon-based metal-free catalysts in electrochemical oxygen oxygen oxygen evolution reaction (OER) has difficulties in structural control and active site characterization, resulting in the development of efficient, stable and low-cost carbon-based metal-free OER catalysts facing major challenge.
Using heteroatom-free, defect-free and metal-free chiral single-walled carbon nanotubes (6,5)-SWNTs and (7,6)-SWNTs as OER high-efficiency catalysts, amorphous carbon is removed by purification, utilizing its unique The band gap structure was studied for electrocatalytic performance.
Achieved efficient electrocatalytic performance, (6,5)-SWNTs exhibited ultra-low overpotential 206mV at 10mA cm-2, with excellent stability and tolerance to CO and toxic KSCN, and water under visible light irradiation The required voltage for the cracking current density is only 1.37V, achieving the optimal OER performance among heteroatom-free doping, defect-free and metal-free carbon catalysts.
Smart Images

Figure CN119284885A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode materials, and particularly relates to the application of chiral single-walled carbon nanotubes in electrochemical oxygen evolution reactions. Background Art
[0002] Electrochemical oxygen evolution reaction (OER), as an anode reaction, plays an important role in rechargeable batteries and water splitting. Efficient OER electrocatalysts are of great significance in these applications. In recent years, efforts to develop efficient OER catalysts have focused on transition metal oxide catalysts, in which metals are widely considered to be active sites. For example, RuO2 and IrO2 are considered benchmark catalysts for OER, but their large-scale commercial application is hindered by the high price and scarce reserves of precious metals. In recent years, carbon-based metal-free catalysts, such as heteroatom doping, surface modification, and defective carbon materials, have been shown to have great potential in improving OER performance through charge / spin redistribution. However, the use of carbon-based metal-free electrocatalysts is complicated by the difficulty in precisely controlling the structure and characterizing the location of active sites. Therefore, the development of efficient, stable, and low-cost carbon-based metal-free OER catalysts remains a major challenge.
[0003] As is known to all, single-walled carbon nanotubes (SWNTs) can be either metallic or semiconducting, depending on their chiral indices (m, n). Specifically, carbon nanotubes with mn=3q (q is an integer) are metallic single-walled carbon nanotubes (m-SWNTs) with a band gap of 0 eV, while all other carbon nanotubes are semiconducting single-walled carbon nanotubes (s-SWNTs) with different band gaps. Current studies have shown that heteroatom-doped carbon nanotubes, surface-modified carbon nanotubes and defective carbon nanotubes can be used as efficient OER catalysts. However, there are technical defects in that it is difficult to precisely control the structure and characterize the active sites after carbon nanotube modification. To date, there are no reports on catalysts of pure carbon nanotubes without heteroatom doping and defects, as well as on their catalytic performance. Summary of the invention
[0004] In view of the above-mentioned technical deficiencies, the present invention provides an application of chiral single-walled carbon nanotubes in electrochemical oxygen evolution reaction. The present invention investigates the relationship between the unique band gap of chiral single-walled carbon nanotubes and OER performance, and for the first time uses non-heteroatom-doped, defect-free and metal-free chiral single-walled carbon nanotubes (6,5)-SWNTs and (7,6)-SWNTs as efficient OER catalysts and as electrode materials to study their electrocatalytic performance.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] Application of chiral single-walled carbon nanotubes in electrochemical oxygen evolution reaction, wherein the chiral single-walled carbon nanotubes are selected from purified (6,5)-SWNTs or purified (7,6)-SWNTs; the purification purpose is to remove amorphous carbon in the chiral single-walled carbon nanotubes.
[0007] Preferably, the chiral single-walled carbon nanotubes are selected from purified (6,5)-SWNTs.
[0008] Preferably, the purification method is: calcining the single-walled carbon nanotube sample in an air atmosphere to remove amorphous carbon, and naturally cooling to room temperature to obtain purified chiral single-walled carbon nanotubes;
[0009] Wherein, the single-walled carbon nanotube sample is selected from (6,5)-SWNTs or (7,6)-SWNTs.
[0010] Preferably, the calcination conditions are: calcination at 200-400° C. for 2-8 hours.
[0011] Preferably, the application method is: using an electrode modified with chiral single-walled carbon nanotubes as an anode, using a commercial Pt / C modified electrode as a cathode, and using a KOH solution as an electrolyte to perform electrolysis.
[0012] Preferably, the modification method is: dispersing chiral single-walled carbon nanotubes in a membrane electrode solution to obtain a slurry, coating the slurry on an electrode, and vacuum drying to obtain an anode.
[0013] Preferably, the membrane electrode solution is a Nafion solution, which is composed of N,N'-dimethylformamide and 10% Nafion, and the volume ratio of N,N'-dimethylformamide to 10% Nafion is 50:1.
[0014] Preferably, the concentration of the KOH solution is 0.1-1 mol / L.
[0015] Preferably, the loading amount of the chiral single-walled carbon nanotubes on the electrode is 1.5-2.5 mg / cm 2 .
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] 1. This application firstly utilizes the unique band gap of single-walled carbon nanotubes and uses single-walled carbon nanotubes without heteroatom doping, defects and metal to achieve efficient electrocatalytic performance. The (6,5)-SWNTs have a high electrocatalytic performance at 10 mA cm -2The (6,5)-SWNTs exhibited an ultra-low overpotential of 206 mV under visible light irradiation, and had excellent stability and tolerance to CO and toxic KSCN. The (6,5)-SWNTs also had improved electrocatalytic performance under photoinduced irradiation. Under visible light irradiation, the (6,5)-SWNTs reached 10 mA cm -2 The voltage required for the water splitting current density is only 1.37 V. As far as we know, among the non-heteroatom-doped, defect-free and metal-free carbon catalysts, the (6,5)-SWNTs of this application currently have the best OER performance.
[0018] 2. This application utilizes the unique electronic structure of single-walled carbon nanotubes and adopts single-walled carbon nanotubes without heteroatom doping, defects and metal-carbon catalysts to rationally design and develop a water splitting device and a metal-air battery. The research of this application is universal and can be used to guide the design and development of carbon-based metal-free electrocatalysts, and can provide theoretical support for other types of electrochemical reactions, not just limited to OER.
[0019] 3. In this application, three different semiconductor single-walled carbon nanotubes were selected for research, namely (6,5)-SWNTs, (7,6)-SWNTs and s-SWNTs, with band gaps of 1.23eV, 1.07eV and 0.68eV respectively. In addition, metal single-walled carbon nanotubes m-SWNTs were also used for comparative research to prove that E e This provides a theoretical basis for the relationship between (electronic energy levels of carbon nanotubes) and OER performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 In the figure, (a) is a scanning electron microscope image of (6,5)-SWNTs of Example 1, and the inset is a transmission electron microscope image of (6,5)-SWNTs; (b) is an X-ray photoelectron spectrum of (6,5)-SWNTs of Example 1; (c) is a Raman spectrum of (6,5)-SWNTs of Example 1, (7,6)-SWNTs of Example 2, s-SWNTs of Comparative Example 1, and m-SWNTs of Comparative Example 2 excited at 633 nm; (d) is an electron spectrophotometer of (6,5)-SWNTs, (7,6)-SWNTs, s-SWNTs, and m-SWNTs based on ultraviolet absorption spectra, and the inset is a schematic diagram of DOS in m- and s-SWNTs;
[0021] Figure 2 In the figure, (a) is the scanning electron microscope image of (7,6)-SWNTs, (b) is the scanning electron microscope image of s-SWNTs, and (c) is the scanning electron microscope image of m-SWNTs. The illustrations in Figures (a), (b), and (c) are the corresponding transmission electron microscope images;
[0022] Figure 3 In the figure, (a) is the X-ray photoelectron spectrum of (7,6)-SWNTs; (b) is the X-ray photoelectron spectrum of s-SWNTs; (c) is the X-ray photoelectron spectrum of m-SWNTs;
[0023] Figure 4 In the figure, (a) is the OER polarization curve of (6,5)-SWNTs, (7,6)-SWNTs, s-SWNTs, m-SWNTs and commercial RuO2; (b) is the specific activity diagram of (6,5)-SWNTs, (7,6)-SWNTs, s-SWNTs, and m-SWNTs; (c) is the O2 precipitation diagram of (6,5)-SWNTs during the OER process; (d) is the stability diagram of (6,5)-SWNTs based on it measurement, and the inset is the experimental diagram of resistance to KSCN and CO ; (e) is a schematic diagram of the effect of pyrene doping on the conduction band of (6,5)-SWNTs; (f) is a schematic diagram of the effect of TCNQ (7,7,8,8-tetracyanoquinodimethane) doping on the valence band of m-SWNTs; (g) is a diagram showing the relationship between the electronic energy level and overpotential of (6,5)-SWNTs, (7,6)-SWNTs, s-SWNTs, and m-SWNTs before and after doping; (h) is a diagram showing the electron energy level of (6,5)-SWNTs, (7,6)-SWNTs, s-SWNTs, and m-SWNTs at 10 mA cm -2 The overpotential trend diagram measured at and the theoretical deviation value ΔE of the electron energy level;
[0024] Figure 5 Linear sweep voltammetry curves (LSV curves) of OER of electrodes with different loading amounts of (6,5)-SWNTs;
[0025] Figure 6 Cyclic voltammetry curves in 1.0 mol / L KOH solution at a scan rate of 20-100 mV / s, where (a) is the cyclic voltammetry curve of the (6,5)-SWNTs sample; (b) is the cyclic voltammetry curve of the (7,6)-SWNTs sample; (c) is the cyclic voltammetry curve of s-SWNTs; (d) is the cyclic voltammetry curve of m-SWNTs;
[0026] Figure 7 In the figure, (a) is a diagram of the photo-assisted electrocatalytic mechanism of (6,5)-SWNTs samples; (b) is a diagram of the OER polarization curves of (6,5)-SWNTs and commercial RuO2 under illumination and no illumination conditions; (c) is a diagram of the transient current density of (6,5)-SWNTs under potential of 1.23V vs RHE pulse light irradiation;
[0027] Figure 8In the figure, (a) and (c) are the OER polarization curves of (7,6)-SWNTs and s-SWNTs, respectively; (b) and (d) are the transient current density diagrams of (7,6)-SWNTs and s-SWNTs under the potential of 1.23 V vs RHE pulse light irradiation, respectively;
[0028] Fig. 9 In the figure, (a) and (c) are the OER polarization curves of graphene and multi-walled carbon nanotubes under illumination and no illumination, respectively; (b) and (d) are the transient current density diagrams of graphene and multi-walled carbon nanotubes under potential of 1.23 V vs RHE pulse light irradiation, respectively;
[0029] Fig.10 A diagram of a water splitting device using (6,5)-SWNTs.
[0030] Fig.11 In the figure, (a) is the water splitting performance of (6,5)-SWNTs||commercial Pt / C in 1.0 mol / L KOH under illumination and without illumination; (b) is the open circuit diagram of the zinc-air battery test using (6,5)-SWNTs; (c) is the zinc-air battery at 3 mA cm -2 Charging test diagram under current density. DETAILED DESCRIPTION
[0031] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0032] Raw materials: (6,5)-SWNTs, carbonyl content ≥ 95%, average diameter 0.78nm;
[0033] (7,6)-SWNTs, carbonyl content ≥95%, average diameter 0.83 nm; both purchased from Sigma-Aldrich;
[0034] Semiconductor single-walled carbon nanotubes, 99% thick film, wherein the semiconductor single-walled carbon nanotubes are a mixture of several semiconductor single-walled carbon nanotubes; metallic single-walled carbon nanotubes, 99% thick film; both are purchased from NanoIntegris.
[0035] Considering the great potential of carbon-based metal-free electrocatalysts in the electrochemical oxygen evolution reaction (OER), in order to create OER active sites, carbon nanotubes currently usually need to be doped with heteroatoms or introduce defects, or be surface-modified. However, in this application, it is found that (6,5)-SWNTs and (7,6)-SWNTs can also show excellent OER performance without heteroatom doping or introduction of defects, or without surface modification; for example, (6,5)-SWNTs at 10 mA cm -2 It has an ultra-low overpotential of 206mV, as well as excellent stability and resistance to KSCN toxicity. In addition, we also found that at 10mAcm -2 At a water splitting current density of 10 mA cm-1, the OER overpotential of (6,5)-SWNTs was as low as -30 mV. -2 When the battery voltage is 1.37V, the corresponding battery voltage is only 1.37V.
[0036] The excellent OER performance of (6,5)-SWNTs is attributed to their ideal S in the van Hove singularity band gap. 11 Bandgap and S 22 Band gap. Among them, S 11 The band gap is 1.23 eV, which is close to the redox state of water (2λ, 1.20 eV). Therefore, by applying a small overpotential, the electronic energy level of (6,5)-SWNTs can be reduced to below the reduced state of water, allowing the oxidation reaction to occur smoothly. 22 The band gap is 2.15 eV, and the electrons in its valence band can be excited to S under visible light. 22 In the conduction band, holes are generated and transferred to S 11 In the valence band, the electrons in the reduced state of water are added to the hole, which is further conducive to the occurrence of water oxidation reaction. The discovery of the influence of this band gap matching on the electrocatalytic process provides a reasonable strategy for the design and development of metal-free carbon catalysts. The catalyst of pure single-walled carbon nanotubes without heteroatom doping and defects proposed in this application has potential application value in alkaline OER electrocatalysis, acidic OER electrocatalysis, and other aspects.
[0037] Example 1
[0038] The method for preparing purified single-walled carbon nanotubes comprises the following steps:
[0039] 10 mg of (6,5)-SWNTs were placed in a quartz cabinet and then calcined at 350° C. in an air atmosphere for 3 h to remove amorphous carbon. After naturally cooling to room temperature, purified (6,5)-SWNTs were obtained, which were recorded as (6,5)-SWNTs.
[0040] Example 2
[0041] The method for preparing purified single-walled carbon nanotubes comprises the following steps:
[0042] 10 mg of (7,6)-SWNTs were placed in a quartz cabinet and then calcined at 350° C. in an air atmosphere for 3 h to remove amorphous carbon. After naturally cooling to room temperature, purified (7,6)-SWNTs were obtained, which were recorded as (7,6)-SWNTs.
[0043] Example 3
[0044] The method for preparing purified single-walled carbon nanotubes comprises the following steps:
[0045] 10 mg of (6,5)-SWNTs were placed in a quartz cabinet and then calcined at 200° C. in an air atmosphere for 8 h to remove amorphous carbon. After naturally cooling to room temperature, purified (6,5)-SWNTs were obtained.
[0046] Example 4
[0047] The method for preparing purified single-walled carbon nanotubes comprises the following steps:
[0048] 10 mg of (6,5)-SWNTs were placed in a quartz cabinet and then calcined at 400° C. in an air atmosphere for 2 h to remove amorphous carbon. After naturally cooling to room temperature, purified (6,5)-SWNTs were obtained.
[0049] Comparative Example 1
[0050] The method for preparing purified semiconductor single-walled carbon nanotubes comprises the following steps:
[0051] 10 mg of semiconductor single-walled carbon nanotubes were placed in a quartz cabinet and then calcined at 350°C in an air atmosphere for 3 hours to remove amorphous carbon. After naturally cooling to room temperature, purified semiconductor single-walled carbon nanotubes were obtained, which were recorded as s-SWNTs. In s-SWNTs, m'-n'≠3q, and q is an integer.
[0052] Comparative Example 2
[0053] The method for preparing purified metallic single-walled carbon nanotubes comprises the following steps:
[0054] 10 mg of metallic single-walled carbon nanotubes were placed in a quartz cabinet and then calcined at 350° C. in an air atmosphere for 3 h to remove amorphous carbon. After naturally cooling to room temperature, purified metallic single-walled carbon nanotubes were obtained, which were recorded as m-SWNTs.
[0055] Results and Discussion
[0056] 1. Test method:
[0057] Characterization: Morphological images were obtained using SEM (Hitachi S-4800, Japan) and TEM (FEI Talos f200X); the composition of the catalysts was studied using XPS (PHI5000 VersaProbeIII XPS, ULVAC-PHI); Raman spectra were recorded under a 633 nm excitation source using a hormone-type HR800 Raman microscope.
[0058] Electrochemical performance measurement method: 2 mg of (6,5)-SWNTs, (7,6)-SWNTs, s-SWNTs, and m-SWNTs were dispersed in the membrane electrode solution, which was a Nafion solution consisting of N,N'-dimethylformamide (DMF, 1 mL) and 20 μL of 10% Nafion, with a volume ratio of 50:1. The solution was then dispersed for 7 days under stirring and ultrasonic treatment until a uniform slurry like ink was obtained. The slurry was dripped on the electrode and dried in air to form a carbon film. The area of the electrode was 1.0×1.0 cm 2 The loading amount of slurry on the electrode is 2 mg / cm 2 The voltammetric measurements were performed on a CHI 660E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.). A standard three-electrode system was used. The standard three-electrode system used a carbon film as the working electrode, a platinum sheet as the auxiliary electrode, and an Ag / AgCl electrode as the reference electrode. The three electrodes were placed in a 1.0 mol / L KOH solution at 10 mV s -1 At a scan rate of , a linear potential scan was used to record the polarization curve. All potentials in this application refer to the standard hydrogen electrode (RHE) potential by converting the potential obtained by the Ag / AgCl electrode to the standard hydrogen electrode (RHE) potential. The specific calculation equation is:
[0059] E vsRHE =E vsAg / AgCl +0.198V+0.059pH.
[0060] Battery performance test method: The (6,5)-SWNTs modified electrode was used as the anode, and the commercial Pt / C modified electrode was used as the cathode. The area of the anode and cathode electrodes was 1.0×0.5cm 2 , the loading amount is 2mg / cm 2 , water decomposition test was carried out using a two-electrode system in 1.0 mol / L KOH solution.
[0061] The zinc plate is used as the anode, and the area of the zinc plate is 2.0×1.0cm 2The air cathode was modified with (6,5)-SWNTs and commercial Pt / C. The (6,5)-SWNTs and Pt / C were mixed in a mass ratio of 1:1. The area of the electrode was 2.0×1.0cm 2 , the loading amount is 2mg / cm 2 The anode and air cathode were placed together in a 6.0 mol / L KOH solution to study zinc-air batteries; constant current charge and discharge experiments were carried out in a mixed solution of 6.0 mol / L KOH and 0.2 mol / L zinc acetate.
[0062] A reversible zinc-air battery was prepared using silicon carbide pre-coated with a mixed solution of (6,5)-SWNTs and commercial Pt / C as the cathode, where the mass ratio of (6,5)-SWNTs to commercial Pt / C was 1:1, and a zinc plate as the anode. The electrolyte filler between the anode and the cathode was a hydrogel polymer electrolyte solution.
[0063] RRDE measurement: A constant voltage of 0.4 V was applied to the Pt ring electrode to cause the oxygen reduction reaction (ORR), and the oxygen generated and detected on the disk electrode during the reduction anodic polarization scan was obtained.
[0064] Electrochemically active specific surface area (ECSA) was calculated at a scan rate of 20–100 mV s -1 When the electrochemical double layer capacitance (Cdl) of the catalyst surface was measured by cyclic voltammogram (CV), the electrochemically active specific surface area of each (6,5)-SWNTs modified electrode was estimated. The ECSA value was calculated according to the following formula:
[0065]
[0066] Cdl is half of the difference between the anodic and cathodic current densities at different scan rates at a potential of 0.1 V vs RHE;
[0067] Calculation method of specific activity: Based on the potential of 1.7V vs The current density (j) under RHE and the electrochemical active specific surface area are calculated as follows:
[0068]
[0069] 2. Conclusion:
[0070] Figure 1 (a) is the scanning electron microscope (SEM) and transmission electron microscope (TEM) images of (6,5)-SWNTs. (6,5)-SWNTs show a characteristic tubular structure with a diameter of about 0.8 nm. Figure 2The (7,6)-SWNTs, s-SWNTs, and m-SWNTs samples also exhibit similar structures and morphologies.
[0071] Figure 1 (b) and Figure 3 The results showed that no metal impurities (Ni, Co, Fe, Mn) were detected by inductively coupled plasma atomic emission spectroscopy (ICP-AES) and x-ray photoelectron spectroscopy (XPS). XPS showed a major C1s peak and a small O1s peak. The oxygen molecules may come from physical adsorption because single-walled carbon nanotubes have sensitive adsorption to O2.
[0072] Figure 1 (c) is the Raman spectra of (6,5)-SWNTs, (7,6)-SWNTs, s-SWNTs, and m-SWNTs. It can be seen that a very weak D band is observed in all four samples. This result shows that the carbon nanotubes have a complete hexagonal lattice and are not doped with heteroatoms. At the same time, for metallic single-walled carbon nanotubes, m-SWNTs conform to the Breit-Wigner-Fano (BWF) characteristics. In contrast, (6,5)-SWNTs, (7,6)-SWNTs, and s-SWNTs all show G modes with relatively short and narrow peaks, which conform to the Lorentz line shape, indicating that (6,5)-SWNTs, (7,6)-SWNTs, and s-SWNTs all have semiconductor properties.
[0073] like Figure 1 As shown in (d), the first band gap (S 11 ), the obtained band gaps are 1.23eV, 1.07eV and 0.68eV from top to bottom respectively; the band gap of m-SWNTs is zero; so the above research shows that the four chiral single-walled carbon nanotubes obtained all have complete tubular structures, similar morphologies and elemental compositions, but different band gaps.
[0074] Linear sweep voltammetry curves (LSV curves) were obtained in 1.0 mol / L KOH solution to study the electrocatalytic oxygen evolution (OER) activities of (6,5)-SWNTs, (7,6)-SWNTs, s-SWNTs, and m-SWNTs samples. Figure 4 As shown in (a), the OER activity increases in the order of m-SWNTs, s-SWNTs, (7,6)-SWNTs, and (6,5)-SWNTs. The OER activity of (6,5)-SWNTs increases in the order of m-SWNTs, s-SWNTs, (7,6)-SWNTs, and (6,5)-SWNTs at 10 mA cm -2 When the overpotential is 206 mV, (6,5)-SWNTs have better OER performance compared with RuO2 (the overpotential of RuO2 is 284 mV) under the same loading.
[0075] The electrochemical double layer capacitance (Cdl) was used to calculate the electrochemically active specific surface area (ECSA), and the specific activities of the four samples (6,5)-SWNTs, (7,6)-SWNTs, s-SWNTs, and m-SWNTs) were calculated using the electrochemically active specific surface area and current density. Figure 6 get Figure 4 (b) Specific activity. The (6,5)-SWNTs has the highest specific activity at 1.7 V, which is 10.24 mA cm -2 , RHE are 2.4, 4.1 and 27.6 times higher than those of (7,6)-SWNTs, s-SWNTs and m-SWNTs, respectively, indicating that (6,5)-SWNTs have excellent intrinsic activity.
[0076] The OER process of (6,5)-SWNTs was further studied using a rotating disk electrode (RRDE). Figure 4 As shown in (c), when the oxidation current on the rotating disk electrode increases, the oxygen reduction reaction (ORR) occurs on the Pt ring electrode, indicating that (6,5)-SWNTs have a high catalytic efficiency. In addition, no hydrogen peroxide was detected at the rotating disk electrode during the OER process, revealing that the OER process of (6,5)-SWNTs is a fast four-electron transfer process, that is, oxygen is produced from water through a four-electron transfer process on the anode.
[0077] The catalytic stability of (6,5)-SWNTs was tested by chronoamperometry. After 10 h of continuous testing, it was shown that the catalytic stability was good and the current only decreased by 6%. Figure 4 (d) as shown in the illustration); and Figure 4 As shown in the Raman spectrum (d), no obvious structural changes were induced with long-term electrolysis, further demonstrating its remarkable catalytic stability. At the same time, when CO was continuously bubbled into the electrolyte (20 mL) for 10 min and 1.0 mL of 10 mmol / L KSCN solution was added to the electrolyte, there was no obvious interference with the current density of (6,5)-SWNTs, indicating that it has a strong affinity for CO and SCN. - ions are well tolerated. It is noteworthy that (6,5)-SWNTs exhibit unprecedented excellent OER performance under alkaline conditions, and even have better catalytic stability compared with most noble metal catalysts (Ir-based, Ru-based and Pt-based noble metal catalysts).
[0078] In order to further study the relationship between the band gap of single-walled carbon nanotubes and the OER catalytic performance, the present application also uses electron-rich molecule pyrene to dope (6,5)-SWNTs, and electron-deficient TCNQ to dope m-SWNTs. The doping method is: the electron-rich molecule pyrene and (6,5)-SWNTs are mixed in a mass ratio of 1:1, and the gap between the conduction band and the valence band is reduced by injecting additional electrons into the conduction band of the semiconductor (6,5)-SWNTs ( Figure 4 (e)); the results show that the disappearance of the UV-visible absorption peak caused by doping confirms its transformation from semiconductor to metallic type; the electron-deficient TCNQ and m-SWNTs were mixed in a mass ratio of 1:1, and as expected, the OER catalytic performance of the material doped with pyrene (6,5)-SWNTs became poor ( Figure 4 (e) In contrast, the OER performance of the electron-deficient TCNQ-doped m-SWNTs material is significantly improved ( Figure 4 (f)), which demonstrates the importance of the band gap of SWNTs for OER catalytic performance, and thus the excellent OER performance of (6,5)-SWNTs can be attributed to their appropriate band gap.
[0079] In order to verify the speculation that the excellent OER performance of (6,5)-SWNTs is attributed to their appropriate band gap, as Figure 4 (g) shows the electronic energy levels of (6,5)-SWNTs, (7,6)-SWNTs, s-SWNTs, and m-SWNTs on the left, and the electronic energy levels expressed in H2O on the right. The λ in the figure is 0.6 eV. The black arrows in the figure indicate the charge transfer from the unoccupied oxidation state (S ox ) is transferred to the electrode; we analyzed the band gap data of single-walled carbon nanotubes and the redox state of water. Taking (6,5)-SWNTs as an example, the Fermi level of (6,5)-SWNTs is different from that of water. When the two phases come into contact, their Fermi levels will automatically match. At this time, by applying a positive potential, the E e (Electron energy level of carbon nanotube) decreases from the top of the valence band, when E e S dropped to water red (reduced state), S red The electrons flow into the newly generated energy band that is not occupied by electrons, and the oxidation reaction occurs smoothly. Since the band gap of (6,5)-SWNTs is exactly 1.23 eV, which is close to the redox value of water (2λ, 1.2 eV), by applying a small overpotential, E e It can be lower than S redSimilarly, (7,6)-SWNTs, s-SWNTs, and m-SWNTs require an overpotential of 95 mV, 290 mV, and 630 mV, respectively, to achieve their E e Move down to S below the water red .
[0080] Obviously, these theoretical overpotentials cannot be accurately determined from the LSV curves due to concentration polarization, the influence of the experimental environment, and the effect of the double-layer current. -2 The following experiment measured the overpotentials of four single-walled carbon nanotube samples to be 206mV, 248mV, 525mV, and 756mV, respectively. Figure 4 As shown in (h), these overpotentials are higher than the corresponding theoretical values, but they have the same trend, which is that they increase with ΔE(E e With solution S red The decrease in the energy gap between the two (between 2 and 3) and the increase in overpotential indicate the close relationship between the band gap and OER performance of non-heteroatom-doped, defect-free, and metal-free single-walled carbon nanotube electrocatalysts, which provides a theoretical guide for the rational design of efficient electrocatalysts based on the energy band structure.
[0081] Figure 5 LSV curves of OER of electrodes with different loadings of (6,5)-SWNTs. Figure 5 It can be seen that the current density increases with the increase of (6,5)-SWNTs loading, but when the loading reaches 2.0 mg / cm 2 After that, the current density tends to be stable with the increase of (6,5)-SWNTs loading, so the optimal loading is determined to be 2.0 mg / cm 2 .
[0082] From the above results, it can be seen that the excellent OER performance of (6,5)-SWNTs is due to its 1.23 eV band gap, which corresponds to the first band gap of the van Hove singularity (S 11 ), while in (6,5)-SWNTs (e.g. Figure 2 (d) and Figure 5 (e) shows that there is a second band gap (S 22 ), and obtain the second band gap (S 22 ) is 2.15eV. S 22 The electrons in the valence band can be easily excited to S by visible light. 22 In the conduction band, holes are generated and transferred to S 11 valence band, so that the electrons in the reduced state of water are added to this hole, such as Figure 7 (a). In this process, the eenergy to further improve the OER performance. As expected, at 10 mA cm -2 When the pulse light is irradiated, the OER overpotential of (6,5)-SWNTs is only -30 mV. Figure 7 As shown in (b), in addition, (6,5)-SWNTs also show higher switching photoelectric response, such as Figure 7 (c). At the same time, Figure 8 As shown, in this study, S 22 The photoinduced OER performance improvement of single-walled carbon nanotubes with a band gap of s-SWNTs and (7,6)-SWNTs is not applicable to single-walled carbon nanotubes without S. 22 Carbon materials with band gaps, such as graphene and multi-walled carbon nanotubes (e.g. Fig. 9 shown).
[0083] To verify the application of (6,5)-SWNTs, we assembled a water electrolysis device with (6,5)-SWNTs anode and Pt / C cathode to generate H2 and O2. Fig.10 As shown; in order to achieve 10mA cm in the absence of lighting -2 The water splitting current density requires a voltage between 1.58V and 1.64V, where 1.64V is the voltage of commercial Pt / C||RuO2. Under visible light illumination, the voltage required to achieve 10mA cm -2 The water splitting current density requires a battery voltage of only 1.37V. Fig.11 As shown in (a), to the best of our knowledge, this result is the best water splitting performance achieved so far by non-heteroatom-doped, defect-free, and metal-free single-walled carbon nanotube electrocatalysts.
[0084] In addition, considering the excellent OER activity of (6,5)-SWNTs, the present application also uses (6,5)-SWNTs as the anode of the zinc-air battery. The zinc-air battery based on (6,5)-SWNTs provides a high open circuit voltage of 1.42V and a stable voltage supply for more than 20h.
[0085] The (6,5)-SWNTs were assembled into zinc-air batteries using the above method. Fig.11 (b) shows that the voltage and an LED bulb are powered by two zinc-air batteries, and the measured voltage is 2.77V, which can be powered by a light-emitting diode (light-emitting diode, 0.04W). At the same time, the charge-discharge cycle experiment shows stable cycle performance. After 18h measurement, the charge-discharge voltage gap only increases by 0.065V, as shown in Fig.11As shown in (c), the electrochemical performance is comparable to that of IrO2||Pt / C catalyst, indicating that (6,5)-SWNTs have great potential in practical applications when used as air anodes in metal-air batteries.
[0086] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention is also intended to include these changes and variations. The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and their protection scope is not limited thereto. Equivalent substitutions or changes made by those skilled in the art on the basis of the present invention are all within the protection scope of the present invention, and the protection scope of the present invention shall be subject to the claims.
Claims
1. Application of chiral single-walled carbon nanotubes in electrochemical oxygen evolution reaction, characterized in that: The chiral single-walled carbon nanotubes are selected from purified (6,5)-SWNTs or purified (7,6)-SWNTs; the purification purpose is to remove amorphous carbon in the chiral single-walled carbon nanotubes.
2. The use of chiral single-walled carbon nanotubes in electrochemical oxygen evolution reaction according to claim 1, characterized in that: The chiral single-walled carbon nanotubes are selected from purified (6,5)-SWNTs.
3. The use of chiral single-walled carbon nanotubes in electrochemical oxygen evolution reaction according to claim 1, characterized in that: The purification method comprises: calcining the single-walled carbon nanotube sample in an air atmosphere to remove amorphous carbon, and naturally cooling the sample to room temperature to obtain purified chiral single-walled carbon nanotubes; Wherein, the single-walled carbon nanotube sample is selected from (6,5)-SWNTs or (7,6)-SWNTs.
4. The use of chiral single-walled carbon nanotubes in electrochemical oxygen evolution reaction according to claim 3, characterized in that: The calcination conditions are: calcination at 200-400°C for 2-8h.
5. The use of chiral single-walled carbon nanotubes in electrochemical oxygen evolution reaction according to claim 1, characterized in that: The application method comprises the following steps: using an electrode modified with chiral single-walled carbon nanotubes as an anode, using an electrode modified with commercial Pt / C as a cathode, and using a KOH solution as an electrolyte to perform electrolysis.
6. The use of chiral single-walled carbon nanotubes in electrochemical oxygen evolution reaction according to claim 5, characterized in that: The modification method is: dispersing chiral single-walled carbon nanotubes in a membrane electrode solution to obtain slurry, coating the slurry on the electrode, and vacuum drying to obtain an anode.
7. The use of chiral single-walled carbon nanotubes in electrochemical oxygen evolution reaction according to claim 6, characterized in that: The membrane electrode solution is a Nafion solution, which is composed of N,N'-dimethylformamide and 10% Nafion, and the volume ratio of N,N'-dimethylformamide to 10% Nafion is 50:
1.
8. The use of chiral single-walled carbon nanotubes in electrochemical oxygen evolution reaction according to claim 5, characterized in that: The concentration of KOH solution is 0.1-1 mol / L.
9. The use of chiral single-walled carbon nanotubes in electrochemical oxygen evolution reaction according to claim 5, characterized in that: The loading amount of the chiral single-walled carbon nanotubes on the electrode is 1.5-2.5 mg / cm 2 .
Citation Information
Patent Citations
Microstructured catalysts and methods of use for producing carbon nanotubes
US20080274036A1
Redox Sorting of Carbon Nanotubes
US20180016148A1
PLATINUM AND TIN OXIDE CO-FUNCTIONALIZED SINGLED WALLED CARBON NANOTUBES (Pt / SnO2 / SWNTs) AND THEIR SENSING PROPERTIES TOWARDS CARBON MONOXIDE AT ROOM TEMPERATURE
WO2018081129A1